The Development Path of Financial Promotion of Science and Technology Innovation in the Context of New Quality Productivity Development - Zhao, Hongxin; Han, Li (Transactions on Economics, Business and Management Research, 2024)
Science and technology innovation is the kernel of developing new quality productivity, and finance has an important role in promoting science and technology innovation. Based on this, this paper studies the path of financial boosting of science and technology innovation, selects the national panel data from 2013 to 2022, adopts the entropy value method to determine the weight of each index and calculate the comprehensive value, and establishes the VAR model of financial input and science and technology innovation development. It is found that 35% of the changes in the development of science and technology innovation can be explained by financial inputs, and further puts forward suggestions to improve the breadth, depth and precision of financial services for science and technology innovation in four aspects: innovating the form of financial inputs, improving the matching precision between financial services and science and technology innovation needs, innovating the financial service system and optimizing the financial ecological environment, so as to provide reference and reference for the formation and development of the development of new-quality productivity.